Improving STEM Capability of Islamic Boarding School Students in Batam Through Robotics Training - Hendawan Soebhakti; Eko Rudiawan Jamzuri; Senanjung Prayoga; Rifqi Amalya Fatekha; Anugerah Wibisana; Susanto Susanto; Riska Analia; Fitriyanti Nakul; Adlian Jefiza; Eka Mutia Lubis; Budiana Budiana; Ika Karlina Laila Nur Suciningtyas; Ahmad Riyad Firdaus (Asosiasi Dosen Pengembang Masyarajat (ADPEMAS) Forum Komunikasi Dosen Peneliti, 2023)
Conducting robotics training as a community service to improve basic knowledge of Science, Technology, Engineering, and Mathematics (STEM) for students is one of the ways to improve their basic knowledge of Science, Technology, Engineering, and Mathematics (STEM) for students is one of the most important aspects of the facing the industrial era 4.0 and society 5.0. Through the Service-Learning approach, this community service by collaborating with Granada International in Batam by involving 29 students, consisting of 7 students from class X, 15 students from class XI, and the rest from class XII, class XI students, and the rest from class XII. The results of mentoring through robotics training were able to increase the average STEM skills of students by 38.15%. In addition, the activity was successfully implemented with participant satisfaction levels above 50% for the subject matter, instructor, and training equipment. Only 17% of the trainees stated that the training time was insufficient, especially for practicum.